Accelerated transformation of macrophage-derived foam cells in the presence of collagen-induced arthritis mice serum is associated with dyslipidemia. (17th February 2016) - Wen, Wen; He, Ming; Liang, Xiao; Gao, Shan-shan; Zhou, Juan; Yuan, Zu-yi
Abstract: Objective : Atherosclerosis characterized by accumulation of foam cells in the arterial intimal layer is accelerated in rheumatoid arthritis (RA) patients. We and others have previously demonstrated that serum from RA patients and collagen-induced arthritis (CIA) mice had proatherogenic features that might lead to progression of atherosclerosis. Here we further examined the effects of serum from CIA mice on the transformation of macrophage-derived foam cells, and investigated potential mechanism. Methods : DBA/1j mice were used to establish CIA model. Murine peritoneal macrophages and macrophage cell line RAW264.7 were treated with different dilute concentrations of mice serum. Results : CIA mice serum increased cholesterol influx and accumulation in murine macrophages, and markedly up-regulated scavenger receptor CD36 expression in the cells, but had no effect on intracellular lipid efflux. Neutralizing monocyte chemotactic protein (MCP)-1, the most significant altered cytokine we observed between normal and CIA mice serum to CIA mice could not reverse these effects. However, administering simvastatin to CIA mice could lower high-density lipoprotein-cholesterol (HDL-C) level and elevate oxidized low-density lipoprotein (ox-LDL) level in CIA mice serum, with attendant decreased lipid accumulation as well as CD36 expression in murine macrophages. Conclusion : Accelerated transformation of macrophage-derived foam cells via up-regulated CD36 expression is related to dyslipidemia rather than elevated inflammatory factor MCP-1 level in CIA mice serum. Decreased HDL-C and higher ox-LDL levels in CIA mice serum may link RA to atherosclerosis.